用因式分解法2x(2+x)=-(x+2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 15:07:57
用因式分解法2x(2+x)=-(x+2)用因式分解法2x(2+x)=-(x+2)用因式分解法2x(2+x)=-(x+2)2x(2+x)=-(x+2)2x(2+x)+(x+2)=0(2x+1)(x+2)
用因式分解法2x(2+x)=-(x+2)
用因式分解法2x(2+x)=-(x+2)
用因式分解法2x(2+x)=-(x+2)
2x(2+x)=-(x+2)
2x(2+x)+(x+2)=0
(2x+1)(x+2)=0
所以2x+1=0
x=﹣1/2
或者
x+2=0
x=﹣2
2x(2+x)=-(x+2)
2x(x+2)+(x+2)=0
(x+2)(2x+1)=0
x1=-2, x2=-0.5
2x(2+x)=-(x+2)
2x(2+x)+(x+2)=0
(2+x)(2x+1)=0
x1=-2 x2=-1/2
因式分解法3(x-2)=x(x-2)
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
(X+2)²=3(X+2) 因式分解法
(2x+1)(x-2)=0因式分解法
因式分解法:9x^2=(x-1)^2
x²+2x=0 因式分解法
因式分解法x的平方-x-2=0
3x^2=7x因式分解法
(x-1)2=1-x 因式分解法
因式分解法解方程.x^2=7x
4x^2-3x=0因式分解法
x^2-20x=-96因式分解法
x(x+1)=5x(x-2)用因式分解法谢谢了
用因式分解法解(2x+3)(x+1)=(x+1)(x+3)
(2x-1)(x+1)=(3x+1)(x+1) 用因式分解法
7x^2+12x+4=0 用因式分解法分解因式
用因式分解法解X^2-6X+ 9=(5-2X)^2
5x(2x+3)=2(2x+3)用因式分解法怎么解